Assessment of urban green spaces proximity to develop the green infrastructure strategy. An Italian case study - Monica Pantaloni; Francesco Botticini; Giovanni Marinelli (TeMA: Journal of Land Use, Mobility and Environment)
To consolidate new models of sustainable growth based on the management of natural resources, the traditional spatial planning tools are being integrated with new approaches based on ecological and environmental "performance" which consider the provision of ecosystem services through the design of Green Infrastructure (GI), a possible way to improve the quality of life in the contemporary city. The paper describes a sectoral study developed on the public green spaces system at the city scale. The work is part of a research project aimed at developing strategic guidelines for Green Infrastructures at the local scale for the definition of the new Urban Green Plan of the Municipality of Falconara Marittima, located in the province of Ancona (center of Italy), selected as a case study. The study provides a method to estimate the proximity of urban green spaces based on the evaluation of their level of accessibility and usability, to maximize the provision of cultural ecosystem services in response to citizen needs. This contribution aims to help public administrations in evaluating the 'performance' of green spaces based on the ecosystem services approach to support urban and territorial planning and decision-making tools.